IMPLEMENTASI KONSEP TRI HITA KARANA DALAM PENDIDIKAN MULTIKULTURAL PADA PEMBELAJARAN IPS SD - I Ketut Manik Asta Jaya; Dewa Bagus Sanjaya; I Wayan Lasmawan (Padma Sari: Jurnal Ilmu Pendidikan, 2026)
The integration of local wisdom into learning has become essential in 21st-century education. This study aims to construct a theoretical argument regarding the alignment between the Tri Hita Karana philosophy and the goals of multicultural education, as well as to formulate a conceptual model that can serve as a reference for educators in creating transformative social studies learning with a diversity perspective. This research employs a narrative review method. Its three main pillars Parahyangan, Pawongan, and Palemahan create a layered framework that builds multicultural awareness starting from a spiritual foundation, manifested in social practice, and extended to the ecological realm. The synergy of these three dimensions produces a multicultural education approach that is not only cognitive but also transformative, shaping students’ character to appreciate diversity across a complete spectrum. It is concluded that implementing the Tri Hita Karana concept in elementary school social studies learning offers a comprehensive and transformative paradigm for multicultural education.